The possibility of granting new legal protection and IP rights to broadcasting organizations against the unauthorized exploitation of their broadcasts - Rafiei, Gholamreza (My University, 2015)
Broadcasting is the final output of the ‘production’ of broadcast signal and its ‘transmission’ to the public. The broadcast’s underlying content could not be received and perceived by the member of public unless it is converted to a signal or a program-carrying signal which is then transmitted. Thus, broadcast signal is not a natural occurrence. Broadcasting organizations are owners of their broadcast signals aside from the ownership in the underlying content. In this relation it does not matter whether the underlying content is an authorial work in copyright or it is a work, which currently falls in the public domain or even a non-protected content in intellectual property law. The use of ‘property’ as a regulatory mechanism to protect ‘broadcast signal’ (as an intangible good) has been accepted in both international and national intellectual property law. Its use conforms to both the character of ‘tradability’ and ‘excludability’ of other, more traditional properties. Several theories exist to justify granting new property-type rights (in the form of the intellectual property-type rights or copyright-like property protection) to broadcast signals. Although few differences may still remain, these justifications are similar to those that exist for protection of authorial works, performances and phonograms. Accordingly, underlying content and broadcast signal are two different subject matters in international copyright and related rights regime and their severability has been proved. Granting new property-type rights to broadcasting organizations with regard to their broadcasts is compatible with the existing technical, structural and functional characteristics and realities of the industry. It should afford broadcasters the ability to control the unauthorized exploitation and unconsented-to dissemination of their broadcast signal over any medium. For, the broadcast signal does not exist only during actual broadcast, it might also be used after the fixation of the broadcast and be placed on online services by the broadcaster itself or by any other unauthorized parties for commercial purposes. Therefore, it is recommended that in a new international norm setting, possibly through adoption of a new WIPO broadcasting treaty, in contrary to the Rome Convention that is a technology-specific instrument, follow a technologically neutral approach in the both platform of origin and platform of exploitation of broadcast signal. In granting new rights and protection, the new treaty should provide that its principal protective mechanism be a ‘mandatory’ ‘exclusionary property protection mechanism’, in other words, granting an exclusive right of authorizing or prohibiting the exploitation of broadcast signal. This mechanism, has already been laid down by the Rome Convention, followed by WPPT (for protection of performers and producers of phonograms) and the WIPO Beijing Treaty and has recently been experimented by numerous national legislations, even in countries that are not party to the Rome Convention, but that have updated the rights and protections conferred to broadcasting organizations. However, in relation to the controversial issues in the negotiation in the WIPO Standing Committee on Copyright and Related Rights (SCCR) including some or all post-fixation rights and the protection of the pre-broadcast signal, technological protection measures and rights management information there are other possible solutions. These solutions or proposals necessarily are not conforming to an individual national law. In this regard, the new WIPO broadcasting treaty can give sufficient freedom with greater flexibilities to its contracting parties which permit different level of discretion, and to decide whether they will grant new proposed rights and protections to broadcasters in their legislation as a mandatory or non-mandatory mechanism. However, the principle of reciprocity may be applied regarding these categories of rights and protections. Since there have been concerns raised about possible consequences of an ‘expansive exclusionary protection mechanisms’ on the public interest, the new treaty may allow for its contracting parties to provide for the same kind of limitations or exceptions with regard to the protection of broadcast signal as they provide for, in their national legislation, in connection with the protection of copyright in literary and artistic works. Founding a new treaty on the ‘exclusionary property-protection mechanism’ or on ‘extended property rights’ over broadcast signal would not prejudice the autonomy of authors and other right holders in the broadcast underlying content. For, they would still be able to disseminate the content itself as they wish, but not derived from the broadcast signal without being first consented to by the broadcasting organization. Finally, acquiring greater property rights for a broadcast signal would not lead to control, either directly or indirectly, over the content itself by broadcasting organizations. The new treaty may include non-prejudice and safeguard clauses to protect copyright and other right holders. In addition, with regard to the broadcast of authorial works and other protected contents, the exercise of the broadcasters’ rights is subject to the rights they acquired from the authors or other right holders.
Thèse de doctorat : Université de Neuchâtel, 2015
Keywords: Diffusion, signal de diffusion; signaux porteurs de programmes; organisme de radiodiffusion; signal antérieur à la diffusion; réémission, retransmission; piraterie diffusée; piratage des signaux; Droits postérieurs a la fixation; communication au public; mise à disposition; services à la demande, droit d'auteur; droits voisins; droits connexes; Comité permanent du droit d'auteur et droits connexes de l'OMPI; Broadcast; broadcast signal; program-carrying signals; broadcasting organization; pre-broadcast signal; rebroadcasting; retransmission; broadcast piracy; signal piracy; post-fixation rights, communication to the public; making available fixation of broadcast; on-demand services; copyright, neighboring rights; related rights; WIPO Standing Committee on Copyright and Related Rights